New types of low-carbon cements with reduced Portland clinker content as a result of ecological actions of cement industry towards sustainable development - Justyna Kuterasińska; Anna Król (Economic and Environmental Studies (E&ES), 2016)
Cement industry is among the most energy-intensive economic sectors. Moreover, significant amounts of carbon dioxide are released to the atmosphere as a result of Portland clinker combustion process, where carbonates (limestone, marl) are the main raw materials applied. To offset the harmful effects of the cement industry on the environment, cement producers have resorted to various ways to reduce greenhouse gas emissions and to reduce energy consumption required to produce cement clinker. Development trends in the area of binding materials aim therefore towards a significant reduction of the Portland clinker content in cements for mineral additives. The outcome of these efforts is an amendment plan to the cement standard EN 197-1 based on the introduction of new composite cement groups CEM II/C and CEM VI characterized by significantly reduced amount of Portland clinker (i.e. ternary cements). The essence of actions takes is to obtain composite cements of a good quality, which, in the wake of the selection of relevant non-clinker constituents combinations, will become an alternative for traditional cements of common use. Hereby paper presents the research results of the 4 new cement types, which confirm the relevance of further development of pro-ecological composite cements.
Keywords: L61; Q42; 330; ternary cements; mineral additives; sustainable development; carbon dioxide emission; cement industry